Implementing Combinative Distance Base Assessment (CODAS) for Selection of Natural Fibre for Long Lasting Composites - Chipade, Amar; Wankhede, Sagar; Pesode, Pralhad; Pawar, Sumod; Gaikwad, Sanjay (Materials science forum, 2023)
Eco-friendly materials are being developed as population change into more aware of the coincidental damage subordinated by synthetic materials. Research investigators have spoken a strong appetite to develop materials capable of replacing synthetic materials. As a result, there has been an increase in exigency for natural fibre-based composites in commercial applications in recent years. Natural fibres are long-lasting materials found in nature that have advantages like renewability, biodegradability, lightweight, high specific characteristics and low cost. To meet client needs in a timely manner, Within the framework of the product design process, the selection of materials should be finished, according to the concurrent engineering strategy. Due to competing requirements, Inappropriate material choice frequently causes untimely failures, which causes large losses. To deal with this objective, selection process of natural fibre for long lasting composites becomes significant. Hence, correct decision-making tool ought to be used. This paper focuses on selection of natural fibre by using CODAS technique. This technique plays a significant role in sensible managing. Since the selection of natural fibre among eight alternatives and six criteria, it was observed that Basalt is best natural for long lasting composites followed by flax and Kenaf respectively when compared with multi-objective optimization and ratio analysis (MOORA) technique.